Actitud hacia el futuro de estudiantes de posgrados. Orientaciones pedagógicas para el desarrollo de competencias cognitivas y socioemocionales (Memorias Sifored - Encuentros Educación UAN, 2021)
The aim is to understand the time profile of postgraduate students and to provide pedagogical guidance. A quantitative and descriptive study was conducted with 102 postgraduate students who completed: Zimbardo's Time Perspective Inventory (1999); 27 students answered a questionnaire on the effects of the COVID-19 pandemic/quarantine on their lives. The results showed three-time styles. The importance of providing an orientation space for student orientation is considered, which facilitates the development of cognitive and socio-emotional competences necessary to face the demands of the context.
Keywords: Time Perspective; Pedagogical Orientation; Cognitive and Socio-emotional Competences; COVID-19